FACTORS AFFECTING POSTPARTUM HAEMORRHAGE ON POSTPARTUM MOTHER - Gustiani, Ria; Kartini, Farida (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2023)
Background: Postpartum haemorrhage in general is defined as blood loss from the body in the amount of 500 ml after vaginal delivery or 1000 ml after cesarian section. Every year it is estimated that there are 140.000 mother’s death caused by PPH or every 4 minutes 1 death occurs worldwide caused by PPH.  According to WHO 99% of all maternal deaths occur in developing countries due to postpartum hemorrhage. Based on data obtained in 2020, the MMR in Indonesia is 305 per 100,000 live births.Purpose: to find out the factors affecting haemorrhage occurrence on postpartum mother based on the results of previous research.Method: Scoping review using databases: Google Schoolar, PubMed, and ProQuest. The keywords used in the literature search are “Factor”, “Postpartum haemorrhage”, “maternity”. The searching results were 7 articles which fulfilled the criteria. The 7 articles then were analyzed by using The Joana Briggs Institute and synthesis method using PEOS modificationResults: Out of 99 articles with relevant title and abstract, obtained 7 articles which fulfilled the inclusion and exclusion criteria. Four factors were found, which are; perineal tear, anemia, placental complications, and uterine atony which affects the haemorrhage on postpartum mother.Conclusion: There are four most frequent factors occurring which affect the occurrence of postpartum haemorrhage namely birth canal tear, anemia factor, placental complication, and uterine atony. Those factors can cause and continuously increase haemorrhage which can lead to maternal mortality rate.